2014
DOI: 10.1242/jcs.151514
|View full text |Cite
|
Sign up to set email alerts
|

PHD3-SUMO conjugation optimizes HIF1 repression independently of PHD3 catalytic activity

Abstract: By controlling HIFa hydroxylation and stability, the prolyl hydroxylase domain (PHD)-containing proteins are essential to the maintenance of oxygen homeostasis; therefore these enzymes are tightly regulated. Small ubiquitin-like modifier (SUMO) is a 10-kDa protein readily conjugated to lysine residues of the targeted proteins in a process termed SUMOylation. In this study, we introduce SUMO conjugation as a novel regulator of PHD3 (also known as EGLN3). PHD3 SUMOylation occurs at a cluster of four lysines at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…In fact, accumulating evidence has revealed that regulation of HIF-1a within NP cells is a complicated process that also involves a promotion of HIF-1a mRNA by PHD3 25 , the PHD2mediated hydroxylation and subsequent degradation of HIF-1a protein 5 , an inhibition of HIF-1a transcriptional activity by FIH-1 40 (factor inhibiting HIF-1), as well as the negative regulation of HIF-1a downstream targets by HIF-2a 9 . Of these hypoxia-responsive proteins, it has been revealed that hypoxia promotes SUMO-2/3 conjugations to PHD3 and this represses HIF-1a transcriptional activity independently of the PHD3 catalytic activity 23 . Similarly, Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, accumulating evidence has revealed that regulation of HIF-1a within NP cells is a complicated process that also involves a promotion of HIF-1a mRNA by PHD3 25 , the PHD2mediated hydroxylation and subsequent degradation of HIF-1a protein 5 , an inhibition of HIF-1a transcriptional activity by FIH-1 40 (factor inhibiting HIF-1), as well as the negative regulation of HIF-1a downstream targets by HIF-2a 9 . Of these hypoxia-responsive proteins, it has been revealed that hypoxia promotes SUMO-2/3 conjugations to PHD3 and this represses HIF-1a transcriptional activity independently of the PHD3 catalytic activity 23 . Similarly, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, SUMO molecules target proteins that share consensus SUMO-acceptor site sequence jKX(D/E), in which j is large hydrophobic residue 15 . Ever since the identification of the first SUMO targeted protein Ran GTPase activating protein 1 (RanGAP1) in 1997 18 , hundreds of functionally diverse substrates have been found to be conjugated by SUMO under both physiological and pathological conditions 15e17 , including the hypoxiaresponsive gene products such as HIF-1a 19 , HIF-2a 20 , HIF-1b 21 , GLUT-1 22 , Prolyl Hydroxylases (PHD3) 23 , and IkBa 24 . Since all of these SUMO substrates respond to and are regulated by hypoxia in NP cells 5,7,9,25,26 , it is not unseasonable to presume that the sumoylation mechanism might be involved in the adaptation of IVD cells to the oxemic and metabolic challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PHDs (PHD1-3) and pVHL have been recognized as the major regulators for modulating hypoxia signaling through regulating the protein stability of HIF-1␣ and HIF-2␣. In fact, it is evident that some factors could affect hypoxia signaling via regulation of PHDs and pVHL (29,31,40,41,43). Although FOXO3a has been reported to affect hypoxia signaling, it has not been shown to directly modulate the major proteins involved in hypoxia signaling, including PHDs and pVHL.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in some cases, it appeared that PHD still had a partial effect on HIF-␣ function under certain hypoxic conditions (29,30); thus, VHL could affect HIF-␣ function as well under these kinds of hypoxic conditions. Because HIF-␣ protein was enhanced, resulting in a higher expression level of hypoxia-inducible genes, it became much easier to evaluate the effect of these gene expressions (29,31), particularly for evaluating the suppression role. To get a clear picture of the role of FOXO3a in hypoxia-inducible gene expression, we further examined the effect of FOXO3a under hypoxia.…”
Section: Vhl Is a Direct Downstream Target Of Foxo3a-mentioning
confidence: 99%
“…The role of PHD3 in controlling HIF-1 transcriptional activity, independent of its hydroxylase function, has been debated. One detailed study has shown that PHD3 promotes HIF-1a ABBREVIATIONS: AF, annulus fibrosus; C-TAD, C-terminal TAD; ChIP, chromatin immunoprecipitation; DASA, N,N9-diarylsulfonamide; ENO1, enolase 1; FIH, factor inhibiting HIF; FBS, fetal bovine serum; GLUT, glucose transporter; HIF, hypoxia inducible factor; HRE, hypoxia response element; HX, hypoxia; JMJD, Jumonji domain-containing protein; Krt19, keratin 19; LDHA, lactate dehydrogenase A; Mf, macrophage; NP, nucleus pulposus; N-TAD, N-terminal TAD; NX, normoxia; ODD, oxygen-dependent degradation domain; PHD, prolyl hydroxylase; PKM, pyruvate kinase muscle; shRNA, short hairpin RNA; TAD, transactivation domain; TEPP, thieno [3,2-b]pyrrole [3,2-d]pyridazinone; WT, wild type transcriptional activity, but a more recent study suggests that PHD3 suppresses HIF-1 activity in a small ubiquitinlike modifier-dependent fashion (14,15). However, the exact nature of this relationship and mechanism of action remain unknown in skeletal tissues, including NP.…”
mentioning
confidence: 99%